Mobile SMS Alerts for Islamic Events and Worships - Al-Salim, Omar Farouk Ahmed (2011)
In the last decade, the mobile phones' usage grown up by an increased number of users, where the mobile phones become a part of people life. The mobile phones today provide more than voice call service. The aim of this project is to help the Muslims to reach the Islamic events and worships using mobile phone technologies by sending SMS messages to their mobile phone devices to stay up to time. The user will subscribe to the services he/she wants to be notified about them. He/she can either choose all of SMS services' types or select the favorite SMS services to him/her.